The Spanish psychology journals: How to choose the right journal to publish. - Carbonell, Xavier; Calvó, Noemí (Anales de Psicología / Annals of Psychology, 2009)
The quality, prestige and influence of a psychological journal are not easy to determine. The most widespread and best known assessment criterion is the impact factor (IF) by the Institute for Scientific Informa-tion (ISI of Thomson-Reuters). Nevertheless, despite its undoubted quali-ties, the IF has many limitations and to use only IF to assess the Spanish psychology journals is confounding. From these considerations, our work is aimed at revising the criteria to assess Spanish psychology journals in order to help authors to choose the suitable journal and thus obtain the best dissemination, prestige and visibility for their work.